Polymorphism analysis of the promoter of cow lactoferrin gene with PCR-RFLP and its correlation with subclinical mastitis - Chang-hong ZHAO; Gao-ming HE; Yan-liang WANG; Zhao-xia ZHANG (Acta Agriculturae Slovenica, 2008)
CMT was used to detect the incidence of mastitis. One hundred twenty cows were selected and assigned into 2 groups, 60 animals in each group: control group (healthy cows), experimental group (cows with subclinical mastitis) and the relationship between cow′s subclinical mastitis and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) of the promoter of cow lactoferrin gene was explored. The results showed that polymorphism existed in the promoter of bovine lactoferrin gene, which suggested that this polymorphism could be associated with mastitis susceptibility.